Lexical Construction of Character Names in the Collection of Short Stories "Robohnya Surau Kami" By A.A. Navis - ., Ermanto; JR, Vicno Triwira Dhika; Ardi, Havid; Juita, Novia (Journal of Ecohumanism, 2024)
This research aims to analyze the lexical construction in the short story collection "Robohnya Surau Kami" by A.A. Navis. The lexical construction that is focused on is the lexical construction of the characters in the short story collection. This research uses a descriptive qualitative approach and a corpus linguistics approach. The corpus linguistic application used in this research is the KORTARA application (Korpus Nusantara). The data collection technique used in this research is documentation techniques, which are sourced from the corpus. The documentation technique used in this research comes from the corpus files contained in the corpus linguistic application (Korpus Nusantara). The corpus target of this research is a short stories corpus. This research uses computational linguistic analysis techniques. The computational linguistic technique in this research goes through several stages, namely identification, classification, interpretation and conclusion Based on the research that has been carried out, several types of character construction have been obtained, namely (1) gender terms, (2) kinship terms in Indonesian, (3) kinship terms in Minangkabau, (4) personal names, (5) country names, (6) common nouns , (7) creator/creator, (8) formal profession/position title, (9) non-formal profession/position title, and (10) pronoun.